Faktor-Faktor yang Mempengaruhi Keputusan Manajemen dalam Pemilihan Perusahaan Outsourcing - Sury Resky Rara'Lebang; Hendra Gunawan (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
Outsourcing has vary in terms of activities being outsourced, reasons for and benefits from outsourcing, and how the decision was made. This research presents an empirical research on five companies. It found out, in most cases it was the peripheral support activities being outsourced with cost reduction as the primary driver. Outsourcing decision was being made early in process without active involvement of the in house provider, and there were problems in supplier selection and management.